Aplikasi Single Index Model dalam Pembentukan Portofolio Optimal Saham LQ45 pada Bursa Efek Indonesia - Atika Lusi Tania (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2019)
Single Index Model is a stock return model that divides the effect on returns into a systematic factor (as measured by yields on the market index) and company-specific factors. The shares used in the formation of the portfolio of the Single Index Model are stocks included in the LQ45 Index in the Indonesia Stock Exchange because this Index has always increased from year to year. However, not all shares in the LQ45 Index can be used, there must be a determination to get the most suitable shares to be used as a portfolio. Therefore, the author uses the Single Index Model Application in the Formation of the LQ45 Optimal Stock Portfolio on the Indonesia Stock Exchange so that investors know how to form an optimal portfolio using a simpler model of the single index model. This study aims to apply the application of a single index model in the formation of a stock portfolio registered in LQ45, determine the proportion of stock investment in the number of lots based on the proportion of stock portfolios, and determine the funds needed for stock investment based on the number of lots. Based on the results of data analysis using the Single Index Model Optimal Portfolio, the results show that out of 45 stocks in LQ45, 13 optimal stocks will be purchased by investors. Thirteen shares and market prices include LPPF Rp.3,400, INTP Rp20,025, LPKR Rp274, INCO Rp3,030, PTPP Rp.2,180, SCMA Rp1,615, TBIG Rp.3,850, AALI Rp.10,350, CTRA Rp1. 070, PWON Rp725, TAXI Rp50, WIKA Rp2,340, and WSKT Rp1,970. The proportion of shares is 9% LPPF, 7% INTP, 5% LPKR, 13% INCO, 19% PTPP, 12% SCMA, 9% TBIG, 7% AALI, 4% CTRA, 6% PWON, 3% TAXI, 4% WIKA , WSKT 2%. The funds to be invested are IDR 1,000,000, the total number of shares to be purchased is 1,271 sheets, or if in the lot lot there are around 12 lots.